Alternative Project Delivery Method Adoption in the AEC Industry: An Organizational Change Perspective. Issue 2 (3rd April 2023) - Aldossari, Khaled M.; Lines, Brian C.; Smithwick, Jake B.; Hurtado, Kristen C.; Sullivan, Kenneth T.
ABSTRACT: In the last two decades, an increasing number of organizations have shifted from using the design-bid-build delivery method (DBB) to alternative project delivery methods (APDMs). This shift requires changes for both the organizations and the individuals involved. This study provides guidelines detailing how to lead APDM adoption at the organizational level through using a change management perspective. The guidelines were developed based on analyzing the results of semi-structured interviews with nine individuals. The participants were industry professionals who were selected because their organizations had successfully adopted APDMs. The findings from the interviews indicate that the best opportunity to implement APDMs successfully is available through using four phases. The phases are preparing and planning, pilot project testing the project, expanding to the intended scale and sustaining and evaluating. The phases include specific organizational change management (OCM) practices that increase the probability of successful APDM adoption. This study contributes to organizational change in the AEC industry by explaining how OCM practices are used to implement APDMs successfully. This study also contributes to the existing body of knowledge by providing guidelines that can help public owner organizations as they consider adopting APDMs for the first time.